Using the Strategic Alignment Model to explore alignment issues between business and IT in a large, financial service organisation in South Africa - Sader, Farhad (Department of Information Systems, 2024)
In 1993, Henderson and Venkatraman proposed a Strategic Alignment Model (SAM) to stimulate thinking about the issue of business and IT alignment from different perspectives. Their model consists of four components across the two dimensions of strategic fit and functional integration, and calls for the recognition of cross domain relationships through four dominant alignment perspectives. Using a qualitative research strategy and a case study methodology, this research used the (SAM) to explore the issue of alignment between business and IT in a large financial services organisation in South Africa. This was achieved by using Henderson and Venkatraman's (1993) characteristics that differentiate strategic alignment from traditional views on linkage as a yardstick to analyse the organisation's perspective on alignment and discuss it in light of the four dominant alignment perspectives identified. A key finding from this study is that while there is an alignment problem, the organisation is going through a transition where it is shifting from a traditional perspective on alignment (strategy execution in terms of Henderson and Venkatraman's (1993) dominant alignment perspectives) towards a more strategic view. As a consequence of this transition, there is a visible disconnect between the rapidly changing expectations on IT and the underlying mechanisms and structures that are required for IT to be able to deliver. This disconnect can be seen as the two are contrasted and compared. While the spark for this change has primarily been a general dissatisfaction with the state of IT, the introduction of new IT leadership has served as a catalyst for provoking the changes that are visible and has essentially become the flywheel that is providing the momentum to drive this change forward. This finding supports and emphasises Hendersen and Venkatraman' s (1993, p.482) assertion that: "The potential for IT impact is so varied and complex that the executive must consider these perspectives as alternative conceptual lenses and be prepared to continuously make adaptations" - but further demonstrates that organisations may struggle as they make these adaptations, particularly if they are going through a process whereby they are broadening their perspective on alignment from strategy execution to something more externally focused. This is particularly because of the inability of structures and processes to keep pace with the rapidly changing expectations of business executives, but also as a result of the potential for conflict to occur as the roles that both IT and business are likely to assume may not be complementary. Furthermore, these roles may differ in terms of the criteria they use to assess performance. In addition to proposing specific recommendations on what the organisation can do to ease the transition from a traditional perspective on alignment towards a more strategic view, this research recommends that Henderson and Venkatraman' s (1993) model be adapted to recognise three further elements that must be considered as part of the strategic alignment equation, namely: (a) values and beliefs; (b) expectations; and, (c) success criteria.